Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Let $x_0,...,x_n$ be distinct real numbers and $l_k(x)$ be the Lagrange's basis function. $δ_n = ∏^n _{k=0}(x-x_k)$. Prove that

a - $\sum^n_{k=0}x^j_kl_k(x) ≡ x^j$. for $j = 0,1,...,n$

b - Let $P_n(x)$ interpolate $f(x)$ at $x_0,...,x_n$. Then $$P_n(x) = \frac{\sum^n_{k=0}f(x_k)/[\delta_n'(x_k)(x-x_k)]}{\sum^n_{k=0}1/[\delta_n'(x_k)(x-x_k)]}$$.

a - From the fact that $\sum^n_{k=0}l_k(x) ≡ 1$ since that the interpolating polynomial $p$ for $f=1$ is the sum $S$ of the Lagrange polynomials. Since $f$ is a polynomial of degree $0$ and the interpolating polynomial is unique: $p = f$. As $p = s$, the sum of the Lagrange polynomials equals one. So from that since $l_k(x)\equiv 1$ then doesn't it follow from that fact it will be $\equiv x^j$? How can I show that using a proof?

b - No idea how to do.

share|cite|improve this question
up vote 2 down vote accepted

For (a), you were on the right track. Suppose you interpolate $f(x) := x^j$ at the nodes $x_0, \ldots, x_n$. The interpolating polynomial is $$ p(x) = \sum_{k=0}^n x_k^j \ell_k(x). $$ Since, as you correctly say, the interpolating polynomial is unique (because the nodes are all distinct) and because $f$ is itself an interpolating polynomial of degree $\leq n$, we must have $p=f$.

For (b), first establish that $\delta_n'(x_j) = \Pi_{k \neq j} (x_j - x_k)$. Then, note that the $j$-th Lagrange polynomial may be written $$ \ell_j(x) = \frac{\delta_n(x)}{\delta_n'(x_j) \ (x - x_j)}. $$ So the interpolating polynomial may be written $$ p(x) = \sum_{j=0}^n f_j \ \ell_j(x) = \delta_n(x) \sum_{j=0}^n \frac{f_j}{\delta_n'(x_j) \ (x - x_j)}. $$ Since $\sum_{j=0}^n \ell_j(x) = 1$, we have, using the expression of $\ell_j$ above $$ 1 = \sum_{j=0}^n \frac{\delta_n(x)}{\delta_n'(x_j) \ (x - x_j)} = \delta_n(x) \sum_{j=0}^n \frac{1}{\delta_n'(x_j) \ (x - x_j)}, $$ and therefore $$ \delta_n(x) = \left( \sum_{j=0}^n \frac{1}{\delta_n'(x_j) \ (x - x_j)} \right)^{-1}. $$

The resulting expression for $p$ is called the barycentric formula. It turns out to be the most useful in practice since it can be computed as cheaply as the Newton interpolant and also updated relatively cheaply if new nodes are added.

A great paper about this form is that of Berrut and Trefethen. It also contains lots of pointers to the literature.

share|cite|improve this answer
Thank you Dominique! For a I have edited to make it more distinguishable. Also for b what do you mean in your very last line "implies using the expression of $l_j(x)$ above $\delta_n(x) = \sum_{j=0}^n \frac{1}{\delta_n'(x_j) \ (x - x_j)}.$?" – user60514 Feb 3 '13 at 4:22
@user60514 : I added a response to (a). Sorry there was an error in the last expression; I forgot to add a "1/..." Let me know if it's clear. – Dominique Feb 3 '13 at 14:00
Yup, it is clearer. Thank you Dominique! – user60514 Feb 3 '13 at 21:03

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.